‘A Woman Was Beating a Man Taking Him by the Forelock’: How a Sacred Thing Became a Comical in Ukraine - Brovarets, Tetiana (Eikón / Imago, 2022)
The paper deals with one famous plot on Ukrainian rushnyks. This is about a scene of beating a man by his wife and the appropriate inscription to it “A woman was beating a man taking him by the forelock”. Notwithstanding the fact that nowadays it is mostly perceived as a humorous scene, the meaning of it may vary up to the sacred one. Is it connected with the fact that Ukrainian rushnyks had been regarded as things of particular significance? The author traces the roots of this embroidered plot in popular culture, showing changing of senses according to the context. Oral culture (folk humorous and dancing songs, narratives, sayings), lubok literature and fictions, Ethnographical features of Ukrainian married men and women are taken into consideration. Also, the issue of renewing the old jokes is considered. When the comic scene became irrelevant or not enough humorous, embroideresses combined it with other scenes to make it more ridiculous. The author concludes that absolutely all folk meanings of one and the same plot have right to exist.